Phase diagram and superconductive properties of splat cooled Cux La1-x. - Favaron, J.; de la Cruz, M. E.; Esquinazi, P.; de la Cruz, F. (American Chemical Society, 1980)
Fil: Favaron, J. Comisión Nacional de Energía Atómica; Argentina